Anisotropic cell growth and cell wall structure in lenticular cell of Valonia utricularis (Ulvophyceae) - Mine, Ichiro; Inoue, Yusuke; Yamamoto, Takuji; Sekida, Satoko (Phycological Research, 2023)
Summary During cell division of the giant‐celled green alga, Valonia utricularis, a lenticular cell is newly formed, which grows from disc‐shaped to globular to obovoid. During the early developmental stages of growth, the cell surface shows a remarkable outward protrusion. In the present study, the anisotropy of cell growth, i.e. the difference between cell surface extension in meridional and radial orientation, was investigated by analyzing the movement of the surface markers in a living cell. Growth was isotropic around the cell zenith but of two different kinds of anisotropic growth in other regions; radial extension was dominant in cell periphery and meridional extension in intermediate regions between zenith and periphery. Moreover, local orientation of cellulose microfibrils was observed on the inner surface of the cell wall during different stages of early development in lenticular cell using an atomic force microscope. Cellulose microfibrils showed meridional orientation overall and this phenomenon was most remarkable in the periphery of the cell, suggesting the possibility of cellulose microfibrils promoting radial extension of cells by suppressing meridional extension of cell wall.